2016
DOI: 10.1111/jch.12864
|View full text |Cite
|
Sign up to set email alerts
|

Strict Blood Pressure Control Achieved Using an ICT‐Based Home Blood Pressure Monitoring System in a Catastrophically Damaged Area After a Disaster

Abstract: 3At the time of the Great East Japan earthquake and tsunami (March 2011), the authors developed a web-based information and communications technology (ICT)-based blood pressure (BP) monitoring system (the Disaster CArdiovascular Prevention [DCAP] Network) and introduced it in an area that was catastrophically damaged (Minamisanriku town) to help control the survivors' BP. Using this system, home BP (HBP) was monitored and the data were automatically transmitted to a central computer database and to the survivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 17 publications
0
40
0
2
Order By: Relevance
“…The telemonitoring system reduced the frequency of patients' visits during the immediate time following the disaster, but did not miss the high-risk patients confined at home. In a stable situation after the acute phase, this system was effective for proactive BP control [97].…”
Section: Disastersmentioning
confidence: 97%
“…The telemonitoring system reduced the frequency of patients' visits during the immediate time following the disaster, but did not miss the high-risk patients confined at home. In a stable situation after the acute phase, this system was effective for proactive BP control [97].…”
Section: Disastersmentioning
confidence: 97%
“…18 The DCAP network is still in use, and strict home BP control has been achieved in most of the 321 eligible patients. 19 Having confirmed that the home BP levels were under control, we have continued to regularly perform 24-hour ambulatory BP monitoring (ABPM) twice-yearly (summer and winter) since the winter of 2012 in the same study population in order to achieve perfect control of not only home BP levels but also 24-hour ambulatory BP levels. 20 The protocol of this study was approved by the ethics committee of the Jichi Medical University School of Medicine.…”
Section: The Minamisanriku Studymentioning
confidence: 97%
“…Seasonal variation in BP could be minimized to around 120 mm Hg in the summer and 125 mm Hg in the winter via anticipation medicine, with the up‐titration of antihypertensive drugs in the autumn months, before the onset of winter (Figure ) . At the time of the Great East Japan earthquake and tsunami (March 2011), the authors developed a web‐based, ICT‐based BP monitoring system (the Disaster CArdiovascular Prevention [DCAP] Network) and introduced it in an area that was catastrophically damaged (Minamisanriku town), in an effort to help control the survivors' BP.…”
Section: Information and Communication Technology (Ict)–based Home Bpmentioning
confidence: 99%